Transforming growth factor β1 inhibition protects from noise-induced hearing loss - Murillo-Cuesta, Silvia; Rodríguez-de la Rosa, Lourdes; Contreras, Julio; Celaya, Adelaida M.; Camarero, Guadalupe; Rivera, Teresa; Varela-Nieto, Isabel (Frontiers in Aging Neuroscience, 2015)
Excessive exposure to noise damages the principal cochlear structures leading to hearing impairment. Inflammatory and immune responses are central mechanisms in cochlear defensive response to noise but, if unregulated, they contribute to inner ear damage and hearing loss. Transforming growth factor ß (TGF-ß) is a key regulator of both responses and high levels of this factor have been associated with cochlear injury in hearing loss animal models. To evaluate the potential of targeting TGF-ß as a therapeutic strategy for preventing or ameliorating noise-induced hearing loss, we studied the auditory function, cochlear morphology, gene expression and oxidative stress markers in mice exposed to noise and treated with TGF-ß1 peptidic inhibitors P17 and P144, just before or immediately after noise insult. Our results indicate that systemic administration of both peptides significantly improved both the evolution of hearing thresholds and the degenerative changes induced by noise-exposure in lateral wall structures. Moreover, treatments ameliorated the inflammatory state and redox balance. These therapeutic effects were dose-dependent and more effective if the TGF-ß1 inhibitors were administered prior to inducing the injury. In conclusion, inhibition of TGF-ß1 actions with antagonistic peptides represents a new, promising therapeutic strategy for the prevention and repair of noise-induced cochlear damage.